Effectiveness of Legal Documentation and Information Network Management at the Secretariat of the Regional People's Representative Council of Pangandaran Regency - Uci Triyanti Dewi; Arie Budiawan; Asep Nurdin Rosihan Anwar (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
In its implementation, the management of the Legal Documentation and Information Network (JDIH) faces a number of obstacles, including the lack of manpower who fully master the management of legal data, the low level of available technological infrastructure, and limited access to legal information for the public. In addition, cooperation between departments that has not been running optimally and a minimal budget are also significant obstacles. The success of JDIH is highly dependent on the availability of resources, a good operational system, and alignment of results with public service objectives. This study aims to evaluate the effectiveness of JDIH management at the Pangandaran Regency DPRD Secretariat. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results of the study indicate that JDIH management has reflected three dimensions of organizational effectiveness according to Lubis and Huseini, namely the source, process, and target approaches. In terms of process and targets, JDIH has shown effectiveness through running SOPs, internal coordination, and several real achievements. However, in terms of resources, strengthening of human resources, infrastructure, and budget is still needed to encourage sustainable effectiveness. Periodic evaluations are also needed to ensure that JDIH management remains relevant to technological developments and community needs. With improvements in the aspects of resources and systemic support, JDIH has the potential to become an open, responsive and adaptive legal information center.